Pressure Drives Rapid Burst‐Like Coordinated Cellular Motion from 3D Cancer Aggregates (Adv. Sci. 6/2022). Issue 6 (24th February 2022) - Raghuraman, Swetha; Schubert, Ann‐Sophie; Bröker, Stephan; Jurado, Alejandro; Müller, Annika; Brandt, Matthias; Vos, Bart E.; Hofemeier, Arne D.; Abbasi, Fatemeh; Stehling, Martin; Wittkowski, Raphael; Ivaska, Johanna; et al.
Abstract : Coordinated Cell Motion In article number 2104808 by Swetha Raghuraman, Timo Betz, and co‐workers, a novel migration phenomenon is presented wherein cancer cells burst out from tumor aggregates as an act of pressure release into the surrounding in‐homogeneous soft extra‐cellular matrix (ECM) made up of collagen. The pressure within tumor aggregates manifests due to cellular swelling, leading to a super‐diffusive coordinated expulsion of cells within 12 hours, directed towards regions providing least mechanical resistance